Justification Strategy in auditing : philosophical and practical View point, for improving the level of external auditor's Performance Quality - الروياتي, عوض (Dirasat in Economics and Business, 2006)
During last twenty years on last century interest was increasing of Auditing Quality , especially in advancing countries ; such as America and England. The Professional Associations in these countries concerned of Quality Control Standards and it used for measuring Auditing Quality , because of difficulties surrounding the measure of this Quality in itself Although these efforts, Auditing Profession still suffers from confidence crisis among external Auditors and users of Accounting information , because of hurts faced by users .On the other hand , Auditing Profession in developing countries suffers from big crisis which is ; neglecting auditor's role by Accounting information users , especially in Libya . so, there is necessity for searching suitable mechanism to enhance Auditing Quality; Justification mechanism and it's supporting factors are the most valuable mechanism for attaining Auditing Quality in real meaning. This study discusses Justification mechanism in Auditing and it's supporting factors through the extent of interest of External Auditor, and Professional and Control Bodies in Libya . The population of this study includes three groups ; Accounting Professors in Libyan Universities, External Auditors and Financial auditing Officers in Public Financial Auditing Council The study has been concluded that External Auditors ,and Financial and Control Bodies in Libya don't interest of Justification mechanism and it's supporting factors . this main conclusion interpreted the weakness of External Auditors performance , which appeared through precedeing studies . In long run if this status of Profession continues , the economic decision in Libya will be hurting Economic development.